Code Switching Used by Certified and Non-Certified English Teachers - Azis, Selvianillah; Rahman, Asfah; Mahmud, Murni (Pascasarjana Universitas Negeri Makassar, 2023)
This research conducted to analyzed the code switching used by certified and non-certified teachers. The researcher applied the qualitative method. The subject of this research was certified and non-certified English teachers at Senior High School 1, 7, and 13 Bone consisted in 2 teachers that were certified and 2 teachers that were non-certified. The data were collected through audio recording, observation checklist, and interviews to find out type of code switching used by teachers, factor of code switching used by teachers, and certified and non-certified English teacher perception of code switching used. The result of this research that there were five types of code switching used by certified teacher in the classroom. They were inter-sentential, intra-sentential, metaphorical, emblematic and establishing continuity switching. Non-certified teachers also used also five types of code switching, they are inter-sentential, intra-sentential, metaphorical, tag and establishing continuity switching. The used of code switching of the teachers dominated by intra-sentential and inter-sentential switching both for certified and non-certified teachers where the usage frequency was over in certified teachers. The occurrence of code switching appears more in certified teachers. The factors of code switching used were intention of clarifying the speech content for interlocutor, repetition used for clarification, translate the unknown vocabulary and talking about particular topic. Certified English teachers perceive that the used of code switching is not directly affected by certification. However, the teacher consciously admits that it affects the teacher's performance when managing the class and in their professional appearance at school. On the other hand non-certified teacher used code switching influenced by their experiences to provide an even understanding for students and main the class situation.